Virtual reality in gait recovery in post stroke patients: a systematic review (Research, Society and Development, 2022)
Physical therapy uses various measures to help people with some neurological deficit recover, including kinesiotherapy, and in recent years there has been growing interest in exercise-based therapy with video games in neurological rehabilitation, non-invasive virtual reality. Virtual reality gives participants the idea that the environment is real and enables reciprocal communication with the dynamic environment created by computers. This study is a systematic review whose general objective was to analyze Virtual Reality in gait recovery in post-stroke patients. Following on from this, this study had as methodology a qualitative and transversal observational systematic analysis of studies that dealt with virtual reality in stroke patients. The result was five articles that objectively demonstrated the effectiveness of Virtual Reality in the recovery of gait in post-stroke patients, compared to other interventions, concluding that VR is essential in the recovery of gait, but it does not overlap with other conventional therapies.